PELATIHAN PEMBUATAN HAND SANITIZER DARI BAHAN ALAMI DAUN SIRIH DAN JERUK NIPIS PADA MASYARAKAT DUKUH GUMULAN KELURAHAN KEMIRI, MOJOSONGO, BOYOLALI - SINTA FATONAH LARASATI; TEGAR HARBRIYANA PUTRA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Community service activities carried out in Gumulan Hamlet aim to provide knowledge about training on making natural hand sanitizers from betel and lime leaves in the midst of the Covid-19 pandemic. The direct benefit of this community service activity is to provide additional knowledge, skills and experience to the people of Gumulan Hamlet by utilizing natural ingredients to make hand sanitizers. This community service activity is carried out in the form of training by providing materials and practices for using natural ingredients as an effort to make natural hand sanitizers. The target audience of this community service activity is the people of Gumulan Hamlet RT02 / RW07. The activity method used in this community service is the method of socialization, question and answer, and discussion.